Redefining the Term “Dialysis” in Efforts to Educate the Public and Eliminate Stigma Against Patients with Chronic Kidney Disease - Humairah Nur Sya’bani; Magrifatul Nasyila Tyandra; Rahma Febianti; Kanaya Azzahra; Muhammad Arief Rekozar (International Journal Labs, 2026)
Chronic Kidney Disease (CKD) has become a global health crisis with an increasing prevalence in Indonesia. Although hemodialysis is a crucial medical procedure to sustain life, the popular use of the term